2023
DOI: 10.1021/acsomega.3c00076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Silica-Supported NiCo Bimetallic Nanocatalysts and Their Enhanced Catalytic Hydrogenation Performance

Abstract: In this work, mesoporous silica SBA-16-supported NiCo bimetallic nanocatalysts were synthesized by coimpregnation of Ni and Co precursors followed by calcination and reduction, and various characterization techniques confirm the formation of NiCo bimetallic nanostructures in the catalysts. The synthesized NiCo/SBA-16 shows enhanced catalytic performance for hydrogenation of a series of nitroaromatics. Under the reaction conditions of 80 °C and 1.0 MPa of H2, the yields of aniline for nitrobenzene hydrogenation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Shi 40 et al reported that magnetic CuNi nanoparticles demonstrated superior catalytic activity and recyclability in the hydrogenation of nitro compounds compared to single metallic Cu and Ni catalysts. In a previous work, 41 Ni–Co bimetallic nanocatalysts supported on mesoporous silica SBA-16 (NiCo 0.3 /SBA-16) exhibited good activity in the hydrogenation of nitroaromatics with a 99% yield of aniline. These studies have demonstrated that bimetallic components can effectively regulate electronic interactions, thereby controlling the bonding strength between particle surfaces and reaction intermediates.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Shi 40 et al reported that magnetic CuNi nanoparticles demonstrated superior catalytic activity and recyclability in the hydrogenation of nitro compounds compared to single metallic Cu and Ni catalysts. In a previous work, 41 Ni–Co bimetallic nanocatalysts supported on mesoporous silica SBA-16 (NiCo 0.3 /SBA-16) exhibited good activity in the hydrogenation of nitroaromatics with a 99% yield of aniline. These studies have demonstrated that bimetallic components can effectively regulate electronic interactions, thereby controlling the bonding strength between particle surfaces and reaction intermediates.…”
Section: Introductionmentioning
confidence: 96%
“…34)-based catalysts, have attracted much attention due to their unique electronic structures and valence changes, among which the spinel-type oxide (AB 2 O 4 ) is the most prominent. AB 2 O 4 has advantages of versatility, flexible ion arrangement, multivalent structure, and higher electronic conductivity, [35][36][37][38] 41 Ni-Co bimetallic nanocatalysts supported on mesoporous silica SBA-16 (NiCo 0.3 /SBA-16) exhibited good activity in the hydrogenation of nitroaromatics with a 99% yield of aniline. These studies have demonstrated that bimetallic components can effectively regulate electronic interactions, thereby controlling the bonding strength between particle surfaces and reaction intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Aniline is an important intermediate in syntheses of organic chemical raw materials that are widely used in organic dyes, pesticides, pharmaceuticals and textiles. 1–7 Nitrobenzene hydrogenation is a common method for industrial aniline production. Traditional metal catalysts generally have high catalytic activity, but often have poor stability and cannot be reused.…”
Section: Introductionmentioning
confidence: 99%
“…The production of CPO from FAL was enhanced in the presence of water as a solvent, and the hydrogenative ring rearrangement was catalyzed by metals . Noble transition metal-based catalysts, especially platinum (Pt), were used for heterogeneous hydrogenation …”
Section: Introductionmentioning
confidence: 99%